Role of comprehensive geriatric assessment in low surgical risk older patients with aortic stenosis - Bo, M.; Bergamo, D.; Calvi, E.; Iacovino, M.; Falcone, Y.; Grisoglio, E.; Salizzoni, S. (Aging clinical and experimental research, 2020)
Background Among elderly with severe aortic stenosis (AS), Comprehensive Geriatric Assessment (CGA) originally contributed to address to transcatheter aortic valve implantation (TAVI) patients not suitable to surgical aortic valve replacement(SAVR). Nevertheless, TAVI has recently been proposed also in lower surgical risk patients. Aims To evaluate predictors of TAVI procedure and clinical outcomes among these patients. Methods For each patient ≥ 65 years with severe AS referring to our Cardiac Surgery Division, CGA was performed, including functional and cognitive status, comorbidity burden, frailty, nutritional status, gait speed, hand-grip strength and number of medications. Surgical risk was evaluated according to the Society of Thoracic Surgeons (STS) score (low-risk < 4%). Post-procedural outcomes (30-day survival and post-procedural complications) were obtained by medical records and a one-year follow-up assessed survival, and functional and cognitive performance. Results Among 154 subjects (mean age 82.9 years), 52 were at low-risk according to STS score. 32 patients were addressed to TAVI, 20 to SAVR. Variables significantly associated with TAVI-approach were lower gait speed ( p 0.030) and higher number of medications ( p 0.015). Short and long-term outcomes did not differ between groups. Discussion Among CGA variables, gait speed and number of medications were associated with the decision to perform TAVI instead of SAVR, even in patients at low surgical risk. 30-day and one-year survival and one-year functional and cognitive decline were similar between groups, despite a relevant prevalence of frailty in the TAVI group. Conclusions We suggest that gait speed and number of medications should be considered in selecting appropriate candidates to TAVI among low surgical risk patients.